2013
DOI: 10.1371/journal.pone.0059661
|View full text |Cite
|
Sign up to set email alerts
|

Egg Laying of Cabbage White Butterfly (Pieris brassicae) on Arabidopsis thaliana Affects Subsequent Performance of the Larvae

Abstract: Plant resistance to the feeding by herbivorous insects has recently been found to be positively or negatively influenced by prior egg deposition. Here we show how crucial it is to conduct experiments on plant responses to herbivory under conditions that simulate natural insect behaviour. We used a well-studied plant – herbivore system, Arabidopsis thaliana and the cabbage white butterfly Pieris brassicae, testing the effects of naturally laid eggs (rather than egg extracts) and allowing larvae to feed gregario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
56
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 38 publications
14
56
0
Order By: Relevance
“…Molecular or chemical changes that could explain the enhanced resistance of naturally oviposited Arabidopsis plants to P.   brassicae larvae were however not identified and further studies should explore this question. On the contrary, levels of a major anti-insect defense metabolite, the 4-methylsulfinylbutyl glucosinolate, and the expression of some glucosinolate biosynthesis genes were significantly reduced in damaged leaves with prior oviposition (Geiselhardt et al 2013), in line with the suppression of herbivore-induced genes found by Bruessow et al (2010). It would be interesting to test if natural oviposition by generalist herbivores that lay eggs on Arabidopsis triggers a similar response and whether a reduced glucosinolate content enhances larval performance, as would be expected from the known role of these metabolites.…”
Section: Egg-induced Plant Defenses and Consequences For Hatching Larvaementioning
confidence: 72%
See 1 more Smart Citation
“…Molecular or chemical changes that could explain the enhanced resistance of naturally oviposited Arabidopsis plants to P.   brassicae larvae were however not identified and further studies should explore this question. On the contrary, levels of a major anti-insect defense metabolite, the 4-methylsulfinylbutyl glucosinolate, and the expression of some glucosinolate biosynthesis genes were significantly reduced in damaged leaves with prior oviposition (Geiselhardt et al 2013), in line with the suppression of herbivore-induced genes found by Bruessow et al (2010). It would be interesting to test if natural oviposition by generalist herbivores that lay eggs on Arabidopsis triggers a similar response and whether a reduced glucosinolate content enhances larval performance, as would be expected from the known role of these metabolites.…”
Section: Egg-induced Plant Defenses and Consequences For Hatching Larvaementioning
confidence: 72%
“…A recent study found that P. brassicae larvae that fed on previously oviposited Arabidopsis plants consumed less leaf material, gained less weight after 2 days and suffered higher mortality than larvae feeding on plants that did not receive eggs (Geiselhardt et al 2013). Surprisingly, these results were different from the study published by Bruessow et al (2010), where P. brassicae egg extract pretreatment did not affect the performance of P. brassicae larvae after 8 days of feeding.…”
Section: Egg-induced Plant Defenses and Consequences For Hatching Larvaementioning
confidence: 99%
“…The egg-induced transcriptional changes of A. thaliana may also provide an ‘alert’ state which prepares the plant for improved anti-herbivore defence if eggs are not removed prior to herbivory. A study by Geiselhardt et al 32,. who did not remove P. brassicae eggs from A. thaliana leaves prior to larval feeding, indicates that eggs are taken as ‘warning’ of impending herbivory; the P. brassicae larvae performed worse on previously egg-deposited than on egg-free leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Eggs from Lepidoptera and Diptera (including Drosophila melanogaster ) can activate PTI and induce ROS accumulation and callose deposition at the site of oviposition (Bruessow et al, 2010; Gouhier-Darimont et al, 2013; Little et al, 2007), leading to reduced larval performance (Geiselhardt et al, 2013). We have here and previously observed the accumulation of ROS at the sites of feeding and oviposition by adult female S. flava , and found that egg deposition activated expression of the PTI marker gene CYP81F2 (Whiteman et al, 2011), which is typically associated with ROS accumulation (Daudi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%